The trade-induced effects of the services Directive and the country of origin principle - de Bruijn, Roland; Kox, Henk; Lejour, Arjan M. (The Hague, 2006)
"The proposed Services Directive by the European Commission could increase intra European trade in commercial services by 30 to 60 percent. This paper analyses the welfare effects of the trade growth using an applied general equilibrium model WorldScan. It shows that GDP could be raised by 0.3 to 0.7 percent and consumption by 0.5 to 1.2 percent in the European Union as a whole. These results could only be realised if the Services Directive is implemented including the country of origin principle. If this principle is excluded from the directive, trade increases only by 20 to 40 percent. The trade-induced welfare effects are correspondingly lower. GDP could rise by 0.2 to 0.4 percent and consumption by 0.3 to 0.7 percent in the EU as a whole. The country-specific effects vary: most of the new Member States will experience larger gains than the average Member State because their services trade is now still hampered by relatively large regulatory barriers in these countries."